Microbial community characterization of ozone-biofiltration systems in drinking water and potable reuse applications. (15th May 2018) - Gerrity, Daniel; Arnold, Mayara; Dickenson, Eric; Moser, Duane; Sackett, Joshua D.; Wert, Eric C.
Abstract: Microbial community structure in the ozone-biofiltration systems of two drinking water and two wastewater treatment facilities was characterized using 16S rRNA gene sequencing. Collectively, these datasets enabled comparisons by facility, water type (drinking water, wastewater), pre-oxidation (ozonation, chlorination), media type (anthracite, activated carbon), media depth, and backwash dynamics. Proteobacteria was the most abundant phylum in drinking water filters, whereas Bacteroidetes, Chloroflexi, Firmicutes, and Planctomycetes were differentially abundant in wastewater filters. A positive correlation was observed between media depth and relative abundance of Cyanobacteria in drinking water filters, but there was only a slight increase in one alpha diversity metric with depth in the wastewater filters. Media type had a significant effect on beta but not alpha diversity in drinking water and wastewater filters. Pre-ozonation caused a significant decrease in alpha diversity in the wastewater filters, but the effect on beta diversity was not statistically significant. An evaluation of backwash dynamics resulted in two notable observations: (1) endosymbionts such as Neochlamydia and Legionella increased in relative abundance following backwashing and (2) nitrogen-fixing Bradyrhizobium dominated the microbial community in wastewater filters operated with infrequent backwashing. Bradyrhizobium is known to generate extracellular polymeric substances (EPS), which may adversely impact biofilter performance and effluent water quality. These findings have important implications for public health and the operation and resiliency of biofiltration systems. Highlights: Cyanobacteria was positively correlated with depth in drinking water filters. Endosymbionts (e.g., Legionella ) were differentially abundant after backwashing. Bradyrhizobium, an EPS producer, may dominate with infrequent backwashing. Pre-ozonation caused a decrease in alpha diversity in wastewater filters. Media type (anthracite vs. carbon) caused significant differences in beta diversity.